Elements of US-Russian relations (Journal of Namibian Studies : History Politics Culture, 2023)
Relations between countries are affected by the elements of strength in each of them, as each country has a number of elements that represent elements of power, and these elements and elements work to strengthen the regional and international role of this country, in a manner that achieves its national security and enhances its national interests regionally and globally, through work In order to invest in the strengths that the state enjoys and overcome the weaknesses it suffers from in a way that leads to determining its international standing, the international political influence, in order to be effective and influential, must be based on a set of conditions that give it a degree of credibility. The state influences the decisions of other states by virtue of its ability, and the power of the state is not limited to military force only, as the traditional approach of interpretation goes, but rather it includes all the state’s material and moral capabilities, and then the state’s strength is explained in terms of its ability to influence externally the behavior of others, and in proportion With the goals of its foreign political movement, in a manner that guarantees it the protection and realization of its national interests.